PENENTUAN TIPE VIRUS EPSTEIN-BARR DALAM BIOPSI JARINGAN NASOFARING PENDERITA NON KARSINOMA NASOFARING DENGAN POLYMERASE CHAIN REACTION (TYPING OF EPSTEIN-BARR VIRUS BY POLYMERASE CHAIN REACTION IN NASOPHARYNGEAL TISSUE - Perpustakaan UGM, i-lib ([Yogyakarta] : SekolahPascasarjana Universitas GadjahMada, 2000)
ABSTRACT Epstein-Barr Virus (EBV) is one of eight herpesvirus family members, commonly infected in humans. Infection EBV affects more than 90% of the human population in the world. EBV is a lymphotropic herpesvirus which also infects and replicates within oropharyngeal epithelial cells. The primary infection often occurs asymtomatically and is followed by the establishment of a lifelong latent infection. EBV strains can be divided into two different types, i.e. types A and B on the basis of organization of their BamHI-WYH and HindllI-E gen regions. The differences between these two types are located on sequence divergence within the open reading frame (ORF) encoding the nuclear antigen EBV (EBNA), i.e. EBNA2, EBNA3, EBNA4, and EBNA6. In general, typing of EBV infecting both NPC and asymptomatic patients in Indonesia, especially in the Special District of Yogyakarta (DIY) has not yet been studied. This work was focused on the presence of EBV type in non-NPC patients (asymtomatic) in DPI based on their gene differences of EBNA2. Biopsies of nasopharyngeal tissues obtained from Dr. Sardjito General Hospital were used as samples. QIMR-WIL cell lines and AG876 DNA were used as positive controls for types A and B, respectively. The deoxyribonucleic acid (DNA) isolated from the biopsies of nasopharyngeal tissues was amplified with polymerase chain reaction (PCR) using a set of specific primers for types A (2A.1/2A.2) and B (2B.1/2B.2) of EBNA2 gene. Amplification products of non-NPC samples indicated that types A and B were 6.5% and 62.5% respectively, both types (A and B) was 12.5% and the remaining of 18.75% were EBV negatif. The further study still needs to be done that will primarily be oriented to determine heterogeneity of other EBNA genes and EBV variant isolated from Yogyakarta area as well.